Diffusion characteristics of dyeing in Polyester fiber garments referred to their mixtures with cotton and composition - Hugo Jiménez-Pacheco (2019)
Currently, textile dyeing companies determine their market according to the raw materials processed, which are based on 100% cotton fibers, these fibers are directed to an exclusive market and therefore these companies establish criteria of high quality standards in each of its processes, dyeing being one of the most demanding due to its fastness parameters and color specifications, these characteristics establish the competitiveness of expanding a product portfolio with the incursion of 100% fiber-based clothing polyester and with cotton blends.Some studies suggest the implementation of the dyeing process of these fibers, allowing the organization to have new production alternatives, dyeing processes for polyester and cotton are carried out with heat treatment between 60 °C and 130 °C respectively, with the use of dispersed and chemical dyes; as in the dyeing of Polyester-Cotton that are made in bathrooms established in each stage. Color and solidity tests are performed according to quality parameters, with light and wash fastness controls. Within these dyeing conditions it is essential to determine the thermal gradients to be applied, whose variable must be controlled to optimize the dyeing of polyester fibers and mixtures.The present study evaluates the pre-treatments and the temperature gradient behavior stage in the dyeing process of polyester fibers, taking into account the dyeing curve, in which only the temperature gradient varies. Mathis-ALT-B equipment is used for the dyeing process, for thermal gradient conditions of 135 °C with gradients of 0.3-4.0 °C/min, rotation speed 40-70 RPM, and as colorants were used Novacron, Terail and Liandisperse for cotton and polyester fibers respectively. The results show that the use of dispersants and anti breakage agents work to prevent failures and improve the corresponding colors, but a high gradient increases the migration of the dye and breaks in the fibers, but in low gradients (2 ° C/min ) The quality of diffusion and dyeing is better and, therefore, prevents reprocessing in the dyeing stage.